Ânforas do Vale do Tejo. As olarias da Quinta do Rouxinol (Seixal) e do Porto dos Cacos (Alcochete) - Raposo, Jorge Manuel Cordeiro; Sabrosa, Armando José Gonçalves; Duarte, Ana Luísa Castanheira (Trabalhos de Antropologia e Etnologia, 2020)
.